Association between polymorphisms of glucocorticoid receptor genes and asthma: A meta-analysis - Fu, Guanglei; Fu, Lijun; Cai, Youli; Zhao, Hui; Fu, Wenjun (Cellular and Molecular Biology, 2018)
Recent studies have evaluated the associations between polymorphisms of glucocorticoid receptor genes and asthma. However, the conclusions of these studies are conflicting. The objective of this meta-analysis was to clarify the association between all known polymorphisms of glucocorticoid receptor genetic loci and susceptibility to asthma, based on existing reports. We conducted a meta-analysis of the association between glucocorticoid receptor polymorphisms (NR3C1) and asthma risk. A systematical literature search was performed in PubMed, EMBASE, Web of Science, China National Knowledge Infrastructure (CNKI), and Cochrane Library until January 15, 2018. The odds ratio (OR), 95% confidence interval (CI), and P value were calculated using Mantel-Haenszel statistics under the allele, homozygote, heterozygote, dominant, or recessive models. P values of less than 0.05 were considered to represent statistically significant associations between glucocorticoid receptor gene polymorphisms and asthma. All statistical analyses were done using the "meta” package (version 4.9–0) of R version 3.4.3 and RStudio version 1.0.44. A total of fourteen studies, reported via ten articles from online databases were included in our meta-analysis. For BclI (from eight studies), a significant association was detected in the allele model, homozygote model, and recessive model (C versus G: OR (95% CI) = 0.63 (0.40–0.97), CC versus GG: OR (95% CI) = 0.41(0.17–0.97), CC versus GC + GG: OR (95% CI) = 0.54(0.34–0.88)), but not in the heterozygote model or the dominant model. For ER22/23EK (from four studies), TthIII1 (from two studies), no significant association was found for any genetic model. After subgroup analyses by age, significant associations were observed for the allele model, homozygote model, dominant model and recessive model for BclI in adults. The ER22/23EK and TthIII1 polymorphisms were not found to be associated with susceptibility to ASTHMA; however, the BclI polymorphisms were significantly associated with ASTHMA in adults.